Central South America - Marengo, J. A. (2017)
The central South America region includes Brazil, Peru, Paraguay, and Bolivia. The 2016 climate conditions were characterized by extreme high temperatures and below-average precipitation in the Amazon and Andean regions, while above-average precipitation was observed in northern Peru and northeastern Paraguay.